SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

High-definition tDCS of the motor cortex affects prefrontal and primary motor activity differently in young and older adults - Yasra Arif; Peihan J. Huang; Seth D. Springer; Hannah J. Okelberry; Jason A. John; Nathan M. Petro; Grant M. Garrison; Kennedy A. Kress; Kellen M. McDonald; Giorgia Picci; Tony W. Wilson (GeroScience, 2025)

Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

Oscillatory Dynamics Serving Verbal Working Memory Differ in People with HIV and Are Linked To Disease Duration - Kellen M. McDonald; Seth D. Springer; Mikki Schantell; Ryan Glesinger; Lucy K. Horne; Hannah J. Okelberry; Jason A. John; Anna T. Coutant; Madelyn P. Willett; Hallie J. Johnson; Rachel K. Spooner; Tony W. Wilson (Journal of Neuroimmune Pharmacology, 2025)
Background Medical advances have greatly improved the quality of life and extended the longevity of people with HIV (PWH). However, many PWH still develop neurocognitive deficits even in the presence of effective viral suppression, with impairments in verbal working memory (VWM) being among the most common. While previous neuroimaging studies have demonstrated altered neural responses during VWM, the underlying temporal dynamics and their relation to clinical indices of HIV remain poorly understood. Hypothesis PWH will have altered neural oscillatory dynamics in brain regions supporting VWM compared to controls, above and beyond the effect of age, and these oscillatory differences will scale with clinical indices of HIV. Methods 166 participants (77 virally-suppressed PWH, 89 demographically-matched controls) completed a VWM task during magnetoencephalography, which was separated into encoding and maintenance phases. Whole-brain, mixed-model ANCOVAs were performed to assess the effects of HIV status on neural dynamics controlling for age. Results PWH performed significantly worse on the task compared to controls. During encoding, there was a significant interaction of group-by-time window, such that PWH had significantly weaker alpha/beta oscillations in the left inferior frontal, superior temporal, and anterior cingulate relative to controls. Further, weaker activity in the anterior cingulate scaled with increased disease duration. PWH also displayed weaker alpha/beta oscillations during maintenance in frontal, temporal, parietal, anterior cingulate, and cerebellar cortices. Conclusions PWH exhibited weaker task-related oscillatory activity during VWM, which was associated with disease duration in the anterior cingulate. Overall, these findings suggest that HIV modulates the neural dynamics underlying VWM, with progressive effects in some areas.

Spatiotemporal Dynamics of Non‐Ecological Speciation in Rubyspot Damselflies ( Hetaerina spp.) - C. Patterson; A. Brennan; H. Cowling; A. González‐Rodríguez; G. F. Grether; L. Mendoza Cuenca; M. Springer; Y. M. Vega‐Sánchez; J. Drury (Molecular Ecology, 2025)
Non‐ecological speciation is a common mode of speciation, which occurs when allopatric lineages diverge in the absence of pronounced ecological differences. Yet, relative to other speciation mechanisms, non‐ecological speciation remains understudied. Numerous damselfly clades are characterised as non‐adaptive radiations (the result of several rounds of non‐ecological speciation without subsequent divergence), but there are few damselfly lineages for which we have a detailed understanding of the spatiotemporal dynamics of divergence. Recent phylogeographic analyses demonstrate that American rubyspot damselflies ( Hetaerina americana sensu lato) actually comprise at least two cryptic lineages that coexist sympatrically across most of Mexico. To broaden our understanding of the dynamics of diversification to other rubyspot lineages, we investigated the phylogeographic history of smoky rubyspot damselflies ( Hetaerina titia ) using genomic data collected across Central and North America. Unexpectedly, we found evidence of reproductive isolation between the highly genetically differentiated Pacific and Atlantic lineages of H. titia in a narrow secondary contact zone on the Isthmus of Tehuantepec, Mexico. We then fit models of historical demography to both H. americana sensu lato and H. titia to place these comparisons in a temporal context. Our findings indicate that Pacific and Atlantic lineages of H. titia split more recently than the broadly sympatric lineages within H. americana sensu lato, supporting key assumptions of the non‐ecological speciation model and demonstrating that these two pairs of sister lineages are at different stages of the speciation cycle.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Identifying the stand properties that support both high biodiversity and carbon storage in German forests - K. Springer; P. Manning; A.L. Boesing; C. Ammer; A.M. Fiore-Donno; M. Fischer; K. Goldmann; G. Le Provost; J. Overmann; L. Ruess; I. Schöning; S. Seibold; et al. (Forest Ecology and Management, 2024)

Identifying the immunoglobulin G transporter in equine tissues: A look at the neonatal Fc receptor - M.C. Guenther; P.P. Borowicz; M.R. Hirchert; P.L. Semanchik; J.L. Simons; J. Fridley; S.H. White-Springer; C.J. Hammer (Journal of Equine Veterinary Science, 2024)

Spatially explicit models reveal rodents rapidly colonize soybean fields regardless of pre-planting chemical treatment timing for cover crop removal - Jena L. Nierman; Sean M. Murphy; Wendy Leuenberger; Allison G. Davis; John J. Cox; Matthew T. Springer (Crop Protection, 2024)

Landscape context and behavioral clustering contribute to flexible habitat selection strategies in a large mammal - Nathan D. Hooven; Kathleen E. Williams; John T. Hast; Joseph R. McDermott; R. Daniel Crank; Matthew T. Springer; John J. Cox (Mammal Research, 2024)

Correlates of mid-winter pregnancy and early reproductive outcomes in a reintroduced elk (Cervus canadensis) population - Nathan D. Hooven; Kathleen E. Williams; John T. Hast; Joseph R. McDermott; R. Daniel Crank; Matthew T. Springer; John J. Cox (Mammalian Biology, 2024)

Non-native plant invasion after fire in western USA varies by functional type and with climate - Janet S. Prevéy; Catherine S. Jarnevich; Ian S. Pearse; Seth M. Munson; Jens T. Stevens; Kevin J. Barrett; Jonathan D. Coop; Michelle A. Day; David Firmage; Paula J. Fornwalt; Katharine M. Haynes; James D. Johnston; et al. (Biological Invasions, 2024)

High-altitude characterization of the Hunga pressure wave with cosmic rays by the HAWC observatory - Ruben Alfaro; César Alvarez; Juan Carlos Arteaga-Velázquez; Arun Babu Kollamparambil Paul; Daniel Avila Rojas; Hugo Alberto Ayala Solares; Rishi Babu; Ernesto Belmont-Moreno; Chad Brisbois; Karen S. Caballero-Mora; Tomás Capistrán; Alberto Carramiñana; et al. (Advances in Space Research, 2024)

Refuge‐yeah or refuge‐nah? Predicting locations of forest resistance and recruitment in a fiery world - Kyle C. Rodman; Kimberley T. Davis; Sean A. Parks; Teresa B. Chapman; Jonathan D. Coop; Jose M. Iniguez; John P. Roccaforte; Andrew J. Sánchez Meador; Judith D. Springer; Camille S. Stevens‐Rumann; Michael T. Stoddard; Amy E. M. Waltz; et al. (Global Change Biology, 2023)
Climate warming, land use change, and altered fire regimes are driving ecological transformations that can have critical effects on Earth's biota. Fire refugia—locations that are burned less frequently or severely than their surroundings—may act as sites of relative stability during this period of rapid change by being resistant to fire and supporting post‐fire recovery in adjacent areas. Because of their value to forest ecosystem persistence, there is an urgent need to anticipate where refugia are most likely to be found and where they align with environmental conditions that support post‐fire tree recruitment. Using biophysical predictors and patterns of burn severity from 1180 recent fire events, we mapped the locations of potential fire refugia across upland conifer forests in the southwestern United States (US) (99,428 km 2 of forest area), a region that is highly vulnerable to fire‐driven transformation. We found that low pre‐fire forest cover, flat slopes or topographic concavities, moderate weather conditions, spring‐season burning, and areas affected by low‐ to moderate‐severity fire within the previous 15 years were most commonly associated with refugia. Based on current (i.e., 2021) conditions, we predicted that 67.6% and 18.1% of conifer forests in our study area would contain refugia under moderate and extreme fire weather, respectively. However, potential refugia were 36.4% (moderate weather) and 31.2% (extreme weather) more common across forests that experienced recent fires, supporting the increased use of prescribed and resource objective fires during moderate weather conditions to promote fire‐resistant landscapes. When overlaid with models of tree recruitment, 23.2% (moderate weather) and 6.4% (extreme weather) of forests were classified as refugia with a high potential to support post‐fire recruitment in the surrounding landscape. These locations may be disproportionately valuable for ecosystem sustainability, providing habitat for fire‐sensitive species and maintaining forest persistence in an increasingly fire‐prone world.

Human perceptions of competing interests in springs ecosystem management on public land in southwestern United States - Andrew J. Lewis; Stefanie Kunze; Julie M. Mueller; Ryan A. Fitch; Abraham E. Springer (Groundwater for Sustainable Development, 2023)

The Past, Present, and Future of Equine Science - Sarah H. White-Springer; Jason Bruemmer; Robert J. Coleman (Journal of Equine Veterinary Science, 2023)

Influence of Mechanistic Target of Rapamycin (mTOR)-Regulated Anabolic Pathways on Equine Skeletal Muscle Health - Pier L. Semanchik; Lauren T. Wesolowski; Patrick J. Ryan; Sarah H. White-Springer; James D. Fluckey (Journal of Equine Veterinary Science, 2023)

Anatomical, Ontogenetic, and Genomic Homologies Guide Reconstructions of the Teeth-to-Baleen Transition in Mysticete Whales - John Gatesy; Eric G. Ekdale; Thomas A. Deméré; Agnese Lanzetti; Jason Randall; Annalisa Berta; Joseph J. El Adli; Mark S. Springer; Michael R. McGowen (Journal of Mammalian Evolution, 2022)

Correction to: Characterizing introgression‑by‑environment interactions using maize near isogenic lines - Zhi Li; Sara B. Tirado; Dnyaneshwar C. Kadam; Lisa Coffey; Nathan D. Miller; Edgar P. Spalding; Aaron J. Lorenz; Natalia de Leon; Shawn M. Kaeppler; Patrick S. Schnable; Nathan M. Springer; Candice N. Hirsch (Theoretical and Applied Genetics, 2021)

Jamaican bioethanol: an environmental and economic life cycle assessment - E. Batuecas; R. Contreras-Lisperguer; C. Mayo; R. Díaz; C. Springer; F. J. Pérez (Clean Technologies and Environmental Policy, 2021)

Urgent plea for global protection of springs - Marco Cantonati; Roderick J. Fensham; Lawrence E. Stevens; Reinhard Gerecke; Douglas S. Glazier; Nico Goldscheider; Robert L. Knight; John S. Richardson; Abraham E. Springer; Klement Tockner (Conservation Biology, 2021)

Characterizing introgression-by-environment interactions using maize near isogenic lines - Zhi Li; Sara B. Tirado; Dnyaneshwar C. Kadam; Lisa Coffey; Nathan D. Miller; Edgar P. Spalding; Aaron J. Lorenz; Natalia de Leon; Shawn M. Kaeppler; Patrick S. Schnable; Nathan M. Springer; Candice N. Hirsch (Theoretical and Applied Genetics, 2020)

10th Anniversary of the European Association for Predictive, Preventive and Personalised (3P) Medicine - EPMA World Congress Supplement 2020 - Olga Golubnitschaja; Ondrej Topolcan; Radek Kucera; Vincenzo Costigliola; M. Akopyan; S. N. Akulov; O Alexandrova; Angel Alonso; Russell J. Andrews; A Assuane Duarte; O. Azarova; Maximilian Babel; et al. (EPMA Journal, 2020)
In 2019, the EPMA celebrated its 10th anniversary at the 5th World Congress in Pilsen, Czech Republic. The history of the International Professional Network dedicated to Predictive, Preventive and Personalised Medicine (PPPM / 3PM) is rich in achievements. Facing the coronavirus COVID-19 pandemic it is getting evident globally that the predictive approach, targeted prevention and personalisation of medical services is the optimal paradigm in healthcare demonstrating the high potential to save lives and to benefit the society as a whole. The EPMA World Congress Supplement 2020 highlights advances in 3P medicine.

Correction to: Review of GPS collar deployments and performance on nonhuman primates - Kerry M. Dore; Malene F. Hansen; Amy R. Klegarth; Claudia Fichtel; Flávia Koch; Andrea Springer; Peter Kappeler; Joyce A. Parga; Tatyana Humle; Christelle Colin; Estelle Raballand; Zhi-Pang Huang; et al. (Primates, 2020)

Review of GPS collar deployments and performance on nonhuman primates - Kerry M. Dore; Malene F. Hansen; Amy R. Klegarth; Claudia Fichtel; Flávia Koch; Andrea Springer; Peter Kappeler; Joyce A. Parga; Tatyana Humle; Christelle Colin; Estelle Raballand; Zhi-Pang Huang; et al. (Primates, 2020)

Effect of removal of bacteria on the biomass and extracellular carbohydrate productivity of Botryococcus braunii - Joao D. Gouveia; Antoine Moers; Yvonne Griekspoor; Lambertus A. M. van den Broek; Jan Springer; Lolke Sijtsma; Detmer Sipkema; Rene H. Wijffels; Maria J. Barbosa (Journal of Applied Phycology, 2019)

Socio-environmental consideration of phosphorus flows in the urban sanitation chain of contrasting cities - Geneviève S. Metson; Steve M. Powers; Rebecca L. Hale; Jesse S. Sayles; Gunilla Öberg; Graham K. MacDonald; Yusuke Kuwayama; Nathaniel P. Springer; Anthony J. Weatherley; Kelly L. Hondula; Kristal Jones; Rubel B. Chowdhury; et al. (Regional Environmental Change, 2018)

Variability in C-reactive protein is associated with cognitive impairment in women living with and without HIV: a longitudinal study - Leah H. Rubin; Lorie Benning; Sheila M. Keating; Philip J. Norris; Jane Burke-Miller; Antonia Savarese; Krithika N. Kumanan; Saria Awadalla; Gayle Springer; Kathyrn Anastos; Mary Young; Joel Milam; et al. (Journal of NeuroVirology, 2018)

Habitat heterogeneity drives the host‐diversity‐begets‐parasite‐diversity relationship: evidence from experimental and field studies - Pieter T. J. Johnson; Chelsea L. Wood; Maxwell B. Joseph; Daniel L. Preston; Sarah E. Haas; Yuri P. Springer (Ecology Letters, 2016)
Despite a century of research into the factors that generate and maintain biodiversity, we know remarkably little about the drivers of parasite diversity. To identify the mechanisms governing parasite diversity, we combined surveys of 8100 amphibian hosts with an outdoor experiment that tested theory developed for free‐living species. Our analyses revealed that parasite diversity increased consistently with host diversity due to habitat (i.e. host) heterogeneity, with secondary contributions from parasite colonisation and host abundance. Results of the experiment, in which host diversity was manipulated while parasite colonisation and host abundance were fixed, further reinforced this conclusion. Finally, the coefficient of host diversity on parasite diversity increased with spatial grain, which was driven by differences in their species–area curves: while host richness quickly saturated, parasite richness continued to increase with neighbourhood size. These results offer mechanistic insights into drivers of parasite diversity and provide a hierarchical framework for multi‐scale disease research.

Erratum to: Low ambient oxygen prevents atherosclerosis - Ju-Gyeong Kang; Ho Joong Sung; Marcelo J. Amar; Milton Pryor; Alan T. Remaley; Michele D. Allen; Audrey C. Noguchi; Danielle A. Springer; Jaeyul Kwon; Jichun Chen; Ji-hoon Park; Ping-yuan Wang; et al. (Journal of Molecular Medicine, 2016)

Low ambient oxygen prevents atherosclerosis - Ju-Gyeong Kang; Ho Joong Sung; Marcelo J. Amar; Milton Pryor; Alan T. Remaley; Michele D. Allen; Audrey C. Noguchi; Danielle A. Springer; Jaeyul Kwon; Jichun Chen; Ji-hoon Park; Ping-yuan Wang; et al. (Journal of Molecular Medicine, 2016)

Localized Prostate Cancer Treatment Decision-Making Information Online: Improving its Effectiveness and Dissemination for Nonprofit and Government-Supported Organizations - Kami J. Silk; Evan K. Perrault; Samantha Nazione; Kristin Pace; Polly Hager; Steven Springer (Journal of Cancer Education, 2013)

An institutional strategy to increase minority recruitment to therapeutic trials - Victoria V. Anwuri; Lannis E. Hall; Katherine Mathews; Brian C. Springer; Jennifer R. Tappenden; Dione M. Farria; Sherrill Jackson; Melody S. Goodman; Timothy J. Eberlein; Graham A. Colditz (Cancer Causes & Control, 2013)

Contrasting effects of sunitinib within in vivo models of metastasis - Jonathan C. Welti; Thomas Powles; Shane Foo; Morgane Gourlaouen; Natasha Preece; Julie Foster; Sophia Frentzas; Demelza Bird; Kevin Sharpe; Antoinette van Weverwijk; David Robertson; Julie Soffe; et al. (Angiogenesis, 2012)

JAX Colony Management System (JCMS): an extensible colony and phenotype data management system - Chuck J. Donnelly; Mike McFarland; Abigail Ames; Beth Sundberg; Dave Springer; Peter Blauth; Carol J. Bult (Mammalian Genome, 2010)

Trend data do support the sequential nature of pinniped and sea otter declines in the North Pacific Ocean, but does it really matter? - J. A. Estes; D. F. Doak; A. M. Springer; T. M. Williams; G. B. Van Vliet (Marine Mammal Science, 2009)

Epibiotic bacteria associated with the recently discovered Yeti crab, Kiwa hirsuta - Shana K. Goffredi; William J. Jones; Hermann Erhlich; Armin Springer; Robert C. Vrijenhoek (Environmental Microbiology, 2008)
Summary The Yeti crab, Kiwa hirsuta Macpherson et al. , is the single known species in a recently discovered crab family Kiwaidae ( Decapoda : Galatheoidea ) from deep‐sea hydrothermal vents. Its chelipeds, walking legs and the ventral surface of its cephalothorax are covered with dense setae that, in turn, are covered with clusters of filamentous bacteria, making the crab appear extraordinarily ‘hairy’. Electron microscopy revealed dense bacterial clusters attached to the chitinous outer layer of the setae. Molecular phylogenetic analyses revealed the setae‐associated bacteria to be dominated by ε‐ Proteobacteria (∼56% of the recovered ribotypes), γ‐ Proteobacteria (∼25%) and Bacteroidetes (∼10%). Fluorescence in situ microscopy confirmed the attachment of filamentous ε‐ Proteobacteria on setae, but no specialized morphological structures appeared to exist for bacterial attachment. Key enzymes involved in the reductive tricarboxylic acid cycle (ATP‐dependent citrate lyase) and sulfite oxidation or dissimilatory sulfate reduction (bidirectional APS reductase) were detected. Consequently, the potential for carbon fixation and cycling of reduced and oxidized sulfur appear to exist in the dense microflora that grows on the crab's setae.

Tracing carbon flow in an arctic marine food web using fatty acid-stable isotope analysis - S. M. Budge; M. J. Wooller; A. M. Springer; S. J. Iverson; C. P. McRoy; G. J. Divoky (Oecologia, 2008)

Mammal‐eating killer whales, industrial whaling, and the sequential megafaunal collapse in the North Pacific Ocean: A reply to critics of Springer et al . 2003 - A. M. Springer; J. A. Estes; G. B. Van Vliet; T. M. Williams; D. F. Doak; E. M. Danner; B. Pfister (Marine Mammal Science, 2008)

Fatty acid signatures of stomach oil and adipose tissue of northern fulmars (Fulmarus glacialis) in Alaska: implications for diet analysis of Procellariiform birds - Shiway W. Wang; Sara J. Iverson; Alan M. Springer; Scott A. Hatch (Journal of Comparative Physiology B, 2007)

Natural selection and mammalian BRCA1 sequences: elucidating functionally important sites relevant to breast cancer susceptibility in humans - Angela Burk-Herrick; Mark Scally; Heather Amrine-Madsen; Michael J. Stanhope; Mark S. Springer (Mammalian Genome, 2006)

Structure–activity relationships in platinum–acridinylthiourea conjugates: effect of the thiourea nonleaving group on drug stability, nucleobase affinity, and in vitro cytotoxicity - Margaret C. Ackley; Colin G. Barry; Amanda M. Mounce; Michael C. Farmer; Beth-Erin Springer; Cynthia S. Day; Marcus W. Wright; Susan J. Berners-Price; Suzanne M. Hess; Ulrich Bierbach (JBIC Journal of Biological Inorganic Chemistry, 2004)

Immunohistochemical Localization of Cardio-Active Neuropeptides in the Heart of a Living Fossil, Nautilus pompilius L. (Cephalopoda, Tetrabranchiata) - J. Springer; P. Ruth; K. Beuerlein; B. Westermann; R. Schipp (Journal of Molecular Histology, 2004)

Molecular Evidence for the Last Survivor of an Ancient Kangaroo Lineage - Michael Westerman; Angela Burk; Heather M. Amrine-Madsen; Gavin J. Prideaux; Judd A. Case; Mark S. Springer (Journal of Mammalian Evolution, 2002)

The Secondary Structure of Mammalian Mitochondrial 16S rRNA Molecules: Refinements Based on a Comparative Phylogenetic Approach - Angela Burk; Emmanuel J. P. Douzery; Mark S. Springer (Journal of Mammalian Evolution, 2002)

Molecular Evidence for the Major Clades of Placental Mammals - Mark Scally; Ole Madsen; Christophe J. Douady; Wilfried W. de Jong; Michael J. Stanhope; Mark S. Springer (Journal of Mammalian Evolution, 2001)

Commentary: External Nasal Cartilages in Bats: Evidence for Microchiropteran Monophyly? - Mark S. Springer; Emma Teeling; Michael J. Stanhope (Journal of Mammalian Evolution, 2001)

Analysis of the first year of Earth rotation parameters with a sub-daily resolution gained at the CODE processing center of the IGS - J. Hefty; M. Rothacher; T. Springer; R. Weber; G. Beutler (Journal of Geodesy, 2000)

An Analysis of Marsupial Interordinal Relationships Based on 12S rRNA, tRNA Valine, 16S rRNA, and Cytochrome b Sequences - Angela Burk; Michael Westerman; Diana J. Kao; John R. Kavanagh; Mark S. Springer (Journal of Mammalian Evolution, 1999)

Cloning and functional analysis of a cDNA encoding a starch synthase from potato ( Solanum tuberosum L.) that is predominantly expressed in leaf tissue - Jens Kossmann; Gernot J. W. Abel; Franziska Springer; James R. Lloyd; Lothar Willmitzer (Planta, 1999)

Determination of the DDE and PCB contents of peregrine Falcon eggs: A comparison of whole egg measurements and estimates derived from eggshell membranes - David B. Peakal'; Thomas S. Lew; Alan M. Springer; Wayman Walker IP; Robert W. Risebrough; J. Geoffrey Monk; Walter M. Jarman; Brian J. Walton; Lincoln M. Reynolds; Richard W. Fyfe; Lloyd F. Kiff (Archives of Environmental Contamination and Toxicology, 1983)

Sex-limited genetic variation in a mouse salivary protein - Robert C. Karn; Stephen R. Dlouhy; Kenneth R. Springer; J. Peter Hjorth; J. Tnnes Nielsen (Biochemical Genetics, 1982)